Reconstrucción de imágenes sísmicas virtuales con técnicas de interferometría en datos de símica pasiva - René Solano Bahena; Rafael Ávila-Carrera; Jorge Aguirre González; Iván Granados Chavarría (Geofísica Internacional, 2023)
This paper aims to obtain compressional body waves (seismic sections) to delimit geological structures associated with hydrocarbon reservoirs. We used a passive seismic dataset from a rectangular array located at northeast of Mexico. Seismic Interferometry (IS) method, which allows extracting the Green’s function by using cross-correlations (CC(t)) of seismic traces was applied. We processed six lines of approximately 8 km length, with 159 geophones each. The obtained CC(t) (also called virtual shots pseudo-sections) were processed with the algorithms that generally are used in the seismic exploration industry to extract the structural and sub-surface velocity information. We regrouped the results of the pseudo-sections of virtual shots by common offset gathers (COG) to generate subsurface images in terms of a zero-offset seismic section. Although, alternative processing algorithms were performed, which consists in applying the wavelet transform method to decompose and reconstruct the CC(t) by means of the Meyer wavelet, improving the quality of the CC(t). Subsequently, new seismic sections were generated considering a common offset. We use offsets of 100, 500, 900, 1300, 1700, and 2100 m among source-receiver virtual arrays. In this case, results were improved substantially, clearly showing the expected reflectors. We observed that the depth of investigation increases for higher offsets, meanwhile the surface resolution decreases. The sections were stacked with the different offsets mentioned above for each line, resulting in a total common offset section. Finally, the obtained sections were compared versus a conventional seismic section (also called “active” seismic sections) migrated in depth.